Impact of a Nutrition-Focused Quality Improvement Intervention on Hospital Length of Stay. Issue 3 (July 2019) - Siegel, Sharon; Fan, Linlin; Goldman, Amanda; Higgins, Joseph; Goates, Scott; Partridge, Jamie
Abstract : Background: Despite its high prevalence, malnutrition in hospitalized patients often goes unrecognized and undertreated. Local Problem: A hospital system sought to improve nutrition care by implementing a quality improvement initiative. Nurses screened patients upon admission using the Malnutrition Screening Tool and initiated oral nutrition supplements for patients at risk. Methods: We retrospectively reviewed the medical records of 20 697 adult patients to determine whether early initiation of nutrition therapy had reduced hospital length of stay and 30-day readmission rates. Results: We found the average time from hospital admission to oral nutrition supplement initiation was reduced by 20 hours (20.8%) after the quality improvement initiative was introduced ( P < .01). Length of stay decreased 0.88 days ( P < .05) more for patients at nutritional risk than patients not at nutritional risk; the probability of 30-day hospital readmission did not differ between groups. Conclusion: These results highlight the importance of adequate nutrition screening, diagnosis, and treatment for hospitalized patients. Abstract : Supplemental Digital Content is Available in the Text.